Comparison of Allergan, Mentor, and Sientra Contoured Cohesive Gel Breast Implants: A Single Surgeon's 10-Year Experience. Issue 5 (November 2015) - Doren, Erin L.; Pierpont, Yvonne N.; Shivers, Steven C.; Berger, Lewis H.
Abstract : Background: Contoured cohesive gel breast implants have been recently approved in the United States. These implants have been available for premarket approval studies for selected surgeons. The purpose of this study was to assess a single surgeon's outcomes in three specific clinical situations—breast augmentation, secondary augmentation, and breast reconstruction—using implants of all three contoured cohesive gel implant manufacturers (Allergan, Mentor, and Sientra) over a 10-year period. Methods: The authors performed a prospective study of contoured cohesive silicone gel breast implants. Demographic and outcomes data were recorded. Complication rates were compared among the three implant manufacturers. Results: From 2001 to 2013, 695 patients were included from U.S. Food and Drug Administration clinical trials. Mean age at implantation was 42.7 years (range, 18 to 82 years), and mean time enrolled was 5.3 years (range, <1 to 10 years). One hundred sixty-four patients (24 percent) received Allergan implants, 245 (35 percent) received Mentor implants, and 286 (41 percent) received Sientra implants. Three hundred eighty-four patients (55 percent) underwent primary augmentation, 198 (29 percent) underwent secondary augmentation, and 113 (16 percent) underwent breast reconstruction. The total complication rate was the lowest for primary augmentation of the Mentor group compared with the Allergan and Sientra groups ( p < 0.05). There were no significant differences in complication rates when used for secondary augmentation and reconstruction. There was no statistically significant difference between implant group reoperation, explantation, or capsular contracture rates. Overall implant rupture and rotation rates were low (0.7 percent and 1.3 percent, respectively). Patient and surgeon satisfaction was high. Conclusions: Contoured cohesive gel breast implants overall have low complication rates and high patient and surgeon satisfaction. The authors believe these implants to be safe and effective in breast augmentation and reconstruction. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III. Abstract : Video Discussion by Matthew M. Hanasono, M.D., is available Online for this article.